The Dötz Benzannulation Reaction: A Booming Methodology for Natural Product Synthesis. Issue 17 (7th May 2020) - Bera, Turban; Pandey, Kartikey; Ali, Rashid
Abstract: Since its finding in 1975, the Dötz benzannulation reaction has attracted a great attention of the scientific community as it permits the regio‐controlled construction of functionalised aromatic frameworks from acyclic precursors. In recent years, this beautifully simple yet much powerful technique for the formation of C−C bonds has opened‐up new possibilities in modern synthetic organic chemistry. In this Review, we report the developments in natural products synthesis by employing the Dötz benzannulation as a key transformation. Although, a flow of publications have witnessed a constant progress in this wonderful area of research, but to our best knowledge this is the first review which purely focuses on the applications of the Dötz benzannulation reaction in natural product synthesis. We are assured that this review will act as a promoter in amplifying the applications of the Dötz benzannulation in the domain of synthetic organic chemistry. Abstract : The Dötz benzannulation reaction is constantly growing due to easy preparation of Fischer carbene complex and its compatibility with diverse functional groups. This reaction occurs under mild reaction conditions with significant chemo‐, regio‐ and diastereoselectivity to generate interesting bioactive targets. In recent years, this fabulous strategy has elevated the modern synthetic organic chemistry to a higher level by replacing various tedious synthetic transformations to generate valuable benzene derivatives.